The optimal dose of Ramelteon for the better treatment adherence of delayed sleep–wake phase disorder: a dropout rate study - Takagi, Shunsuke; Sugihara, Genichi; Takahashi, Hidehiko; Inoue, Yuichi (Frontiers in Neurology, 2023)
Background Evidence regarding the effectiveness of melatonin receptor agonists in treating delayed sleep–wake phase disorder (DSWPD) remains limited. This study aimed to determine the optimal dose of ramelteon, a melatonin receptor agonist, for the better treatment adherence of DSWPD. Methods The patients who were diagnosed definitely as having DSWPD by board-certified physicians specialized in sleep medicine and started to receive strategically timed ramelteon medications after the diagnosis were included. Data on the initial ramelteon dose and follow-up duration (up to 24 months) were collected retrospectively. Patients with treatment discontinuation, changes in ramelteon dose, or the addition of other sleep-related medications were considered dropouts. Kaplan–Meier estimates, log-rank tests, and Cox regression analyses were performed. Results Overall, 373 patients were analyzed. The findings revealed that the 2 mg dose of ramelteon was associated with a lower dropout rate compared to the other doses (8 mg, 4 mg, and 1 mg). The dropout rate for the 2 mg group was estimated to have a hazard ratio (HR) of 0.5762 when compared with the 8 mg dose group. Sex did not reveal a significant HR, whereas older age exhibited a small but significant HR (0.9858). Conclusion For achieving better adherence, a dosing regimen of strategically timed 2 mg ramelteon may be the best for the treatment of DSWPD. The therapeutic dose window for better adherence seems to center approximately 2 mg of ramelteon. Furthermore, caution should be exercised when treating younger patients to prevent dropouts.